2016
DOI: 10.1080/17474124.2016.1193003
|View full text |Cite
|
Sign up to set email alerts
|

Association of long noncoding RNA and c-JUN expression in hepatocellular carcinoma

Abstract: This information sheds light on the possible role of lncRNA-UCA1 and C-JUN mRNA as promising diagnostic and prognostic markers as well as potential therapeutic targets in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…As reported, lncRNAs could discriminate patients with HCC from healthy people with higher accuracy than the existing biomarkers (sensitivity: 91.4% vs 82.8%; specificity: 88.6% vs 82.8%), when combined with AFP, the sensitivity significant raises to 100%. [28] Likewise, a panel of lncRNAs (lncRNA-UCA1 and lncRNA-WRAP53) also achieved a higher accuracy than single lncRNA. [31] However, in contrast to these studies, [30,31,42] the difference in overall sensitivity and specificity was not statistical significant between panels of lncRNAs and single lncRNA in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, lncRNAs could discriminate patients with HCC from healthy people with higher accuracy than the existing biomarkers (sensitivity: 91.4% vs 82.8%; specificity: 88.6% vs 82.8%), when combined with AFP, the sensitivity significant raises to 100%. [28] Likewise, a panel of lncRNAs (lncRNA-UCA1 and lncRNA-WRAP53) also achieved a higher accuracy than single lncRNA. [31] However, in contrast to these studies, [30,31,42] the difference in overall sensitivity and specificity was not statistical significant between panels of lncRNAs and single lncRNA in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that AUC for plasma DANCR was 0.868 which was higher than that for AFP (AUC = 0.744) when differentiating patients with HCC from non-HCC patients [112] . Besides these circulating lncRNAs, JPX, UCA1 and WRAP53 were found increased in HCC patients [106,113,114] alone or in combination with other lncRNAs, miRNAs or serum biomarkers [115] . Many reports have indicated that the deregulation of lncRNAs plays important roles in occurrence and progression of HCC however further studies are needed in order to use these as biomarkers.…”
Section: Circulating Non-coding Rnamentioning
confidence: 99%
“…For example, lncRNA UCA1 can be used to detect HCC with a sensitivity of 91.4% and a specificity of 88.6%. 95 miR-375 levels can also be used to differentiate between healthy individuals and HBV-associated HCC with 96% sensitivity and 100% specificity. 96 Recently, ceRNA networks have been identified in pancreatic cancer and lung adenocarcinoma with the intention of using them as potential biomarkers for diagnosis.…”
Section: Discussionmentioning
confidence: 99%